The indirubin derivative 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE) potently modulates inflammatory cytokine and prostaglandin release from human monocytes through GSK-3 interference - Czapka, Anna; König, Stefanie; Pergola, Carlo; Grune, Christian; Vougogiannopoulou, Konstantina; Skaltsounis, Alexios Leandros; Fischer, Dagmar; Werz, Oliver (Biochemical Pharmacology, 2020)
Indirubin is a natural bis-indole alkaloid contained as active ingredient in the traditional Chinese remedy Danggui Longhui Wan. Indirubin and its 3′-oxime derivatives exhibit anti-cancer and anti-inflammatory properties and they inhibit glycogen synthase kinase (GSK)-3 in cell-free assays where 6-bromoindirubin-3′-oxime (6BIO) is among the most potent analogs. Here, we reveal 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE) as highly potent derivative able to inhibit pro-inflammatory cytokine, chemokine and prostaglandin (PG) release in human primary monocytes while increasing anti-inflammatory interleukin (IL)-10 levels. 6BIGOE suppressed lipopolysaccharide (LPS)-induced IL-1β and PGE2 release with IC50 of 0.008 and 0.02 µM, respectively, being ≥ 12-fold more potent than 6BIO. The effects of 6BIGOE are mediated via intracellular inhibition of GSK-3, where 6BIGOE again surpassed the effectiveness of 6BIO despite the higher potency of the latter in cell-free GSK-3 activity assays. Side-by-side comparison of 6BIGOE (0.1 µM) with the selective GSK-3 inhibitor SB216763 (5 µM) revealed congruent properties such as enrichment of β-catenin and suppression of cyclooxygenase (COX)-2 protein levels due to GSK–3 inhibition. Metabololipidomics using ultra-performance liquid chromatography-tandem mass spectrometry showed that 6BIGOE selectively decreases pro-inflammatory COX-derived product formation without marked modulation of other lipid mediators. In summary, 6BIGOE is a highly potent indirubin derivative in the cellular context that favorably modulates pro- and anti-inflammatory cytokines as well as COX-2-derived PG via interference with GSK-3.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Cytokine; Glycogen synthase kinase-3; Indirubin; Inflammation; Lipid mediator